Unsolved triumph: Cannons and causes of the second Russian turmoil - Dmitriy I. Lukshin, Ajvaz M. Fazliev,; Mariam A. Galeeva, Liliya R. Galimzyanova, (Opción, 2019)
The article presents an original analysis of the main aspects of Russian turmoil of the early XX century via deep study of the traditions of peasant studies and introduction into scientific circulation of new archival documents. In result, the prolonged self-reflection, which already began to look like a nirvana, caused rotting of the discourse, which was not experiencing the invigorating influence of criticism and beneficial influence of dynamics. In conclusion, the picture of community-based revolution, it is rather unsightly. But it is reduced to a banal robbery or to the notorious peasant element, senseless and ruthless Russian revolt.